Eocene conchostracans from the Laney Member of the Green River Formation, Wyoming, USA - Yan-bin, Shen (2006)
Two new species of conchostracans, Cyclestherioides wyomingensis and Prolynceus laneyensis, belonging to the Cyclestheriidae and Lynceidae, respectively, are described from the Eocene Laney Member of the Green River Formation of Wyoming, USA. These are the first Cenozoic fossil conchostracans to be formally reported from North America. Cyclestherioides wyomingensis has a close affinity to the extant Cyclestheria hislopi. The latter is a pan-tropical species, found between approximately 30°N and 35°S. Thus, Cyclestherioides may indicate that the Laney Member was deposited in a subtropical setting. The conchostracans and associated fauna of the Laney Member suggest that this member was deposited nearshore in a shallow lake. The concept of Cyclestherioides is emended and some fossil species referred to this genus are revised